2020
DOI: 10.21203/rs.3.rs-32850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parent feedback: perception of parents and pediatric residents in Asian culture

Abstract: Background Residency programs have used feedback of parents as a part of multisource feedback to improve residents’ skills. However, there is no evidence showing how parents can appropriately be engaged in pediatric resident feedback in our context. This study aimed to investigate: 1) the resident skills assessed by parents in perception of Thai parents and pediatric residents and 2) the parent characteristics making credible feedback in perception of Thai pediatric residents. Methods The participating paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…This is the rst study that has tested the PARENTS reliability and validity in a non-western environment -the previous study in Thailand only used the items in PARENTS for qualitative analysis. 15 Like the Thailand and earlier studies we found that selection of items in PARENTS scale provide a useful feedback mechanism for accessing the NTS of PGRs in an e cient and objective manner. 16,17 The ve items (3, 4, 13, 14 & 15) are related to the skills of the PGR to assess the condition of the child and to be able to explain it to the parent effectively -it also covers basics like hygiene and display of proper identi cation.…”
Section: Discussionsupporting
confidence: 62%
“…This is the rst study that has tested the PARENTS reliability and validity in a non-western environment -the previous study in Thailand only used the items in PARENTS for qualitative analysis. 15 Like the Thailand and earlier studies we found that selection of items in PARENTS scale provide a useful feedback mechanism for accessing the NTS of PGRs in an e cient and objective manner. 16,17 The ve items (3, 4, 13, 14 & 15) are related to the skills of the PGR to assess the condition of the child and to be able to explain it to the parent effectively -it also covers basics like hygiene and display of proper identi cation.…”
Section: Discussionsupporting
confidence: 62%